CAPITAL INVESTMENT, INTERNASIONALISASI, DAN FIRM PERFORMANCE : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Elvinna Salim; Deddy Marciano; Arif Herlambang (Perpustakaan Universitas Surabaya, 2018)
The objective of this study is to examine the effect of capital investment to internationalization and f oreign sales growth and al so the effect of internationalization to firm performance in manufacturing company that listed in the I ndonesia Stock Exchange 2011-2015 period. The dependent variables in this study are internationalization, foreign sales growth, and ROA . Independent variables used are capital investmentandinternationalization, as well as control variables used are industry return, leverage, firm size, fixed assets ratio, market to book value, andsales growth. This study uses 2 regression analysis model, which is linear and quadratic model to test the hypothesis with a sample of 83 industrial manufacturing companies in Indonesia Stock Exchange 2011-2015 period. The numbers of observation used in this study are 415 observations. The result shows that capital investment has a s ignificant negative effect and U-shaped on internationalization of the company, capital investment has a significant positive effect on foreign sales growth of the company. Internationalization has no significant effect on firm performance.